Factors Related to the Incidence of Hypertension Among Hajj Pilgrims from Banjarmasin Indonesia in 2025 - Aqso Ampri Harahap; Kurnia Dwi Artanti; Dimas Agung Trisliatanto (Postgraduate, University of Mataram, 2025)
This study aimed to analyze the factors related to the incidence of hypertension among Hajj pilgrims from Banjarmasin Indonesia in 2025. This study used a quantitative approach with a cross-sectional study design. The sampling technique used total sampling with secondary data, as many as 1050 prospective Hajj pilgrims. Data analysis was carried out using SPSS software. The variable of age range with a p-value of <0.001 and adjusted PR was 6.23 with 95% CI (5.27-8.13). Age 41 to 60 years old had adjusted PR was 3.46 with 95% CI (2.38-5.22). The variable of of diabetes mellitus had a p-value of <0.001 and adjusted PR of 1.74 with 95% CI (1.44-1.95). The variable of hyperlipidemia had a p-value of <0.001 and adjusted PR of 1.36 with 95% CI (1.28-1.59). The variable of heart disease/heart failure with p-value <0.001 and obtained adjusted PR of 1.28 with 95% CI (1.20-1.47). The variable of family history of hypertension with p-value <0.001 and obtained adjusted PR of 1.72 with 95% CI (1.62-1.94). The study concluded that the factors related to hypertension incident in Hajj pilgrims of Banjarmasin Indonesian in 2025, were age range, diabetes mellitus, hyperlipidemia, heart disease/heart failure, and family history of hypertension.